Ngữ pháp tiếng Anh cao cấp = Advanced English grammar : a university course - Lê Minh Cẩn. (Nxb Đồng Nai, 2001)
Basic concepts. The skeleton of the message : introduction to clause structure. The development of the message. Expressing patterns of experience: processes, participants, circumstances. Interaction between speaker and hearer: mood structures of the clause...